Международный английский язык в локальных контекстах глобального развития - Мележик, К.А. (Культура народов Причерноморья, 2014)
В статье рассматривается взаимодействие глобальных и локальных тенденций
характеризующих новые варианты английского языка (АЯ), уточняются прагматические факторы,
регулирующие последовательность этапов их становления, и намечаются основные элементы
парадигмы международного АЯ (МАЯ). МАЯ определяется как универсальный контактный язык
международной коммуникации, предоставляющий равные права всем своим пользователям.
Пользователи МАЯ являются интерактивными субъектами языкового развития, формирующими свой
АЯ и его социолингвистические функции. У статті розглядається взаємодія глобальних і локальних тенденцій, які характеризують
нові варіанти англійської мови (АМ), уточнюються прагматичні фактори, що регулюють послідовність
етапів їх становлення, і намічаються основні елементи парадигми міжнародної АМ. Міжнародна АМ
визначається як нейтральна, універсальна контактна мова міжнародної комунікації, що надає рівні
права всім своїм користувачам. Користувачі міжнародної АМ є інтерактивними суб'єктами процесу
мовного розвитку, які формують як свою АМ, так і її соціолінгвістичні функції. The article discusses the interaction of global and local trends characterizing new variaties of
English: transplantation in new sociocultural conditions, nativization and development of local norms, extension
of functions and socio-territorial diversification. Regular pragmatic factors are claimed to determine the
sequence of stages of new local varieties of English. Understanding of International English paradigm requires
recognition of a number of key factors: equality of all speakers, adaptation of both native and non-native
speakers to mutual intelligibility, development of an international code, dissociation from any particular ethnic
culture, and presence of a nuclear morphosyntactic system. International English belongs to international users
and is not expected to obey native speaker norms. A new definition of International English maintains that it is a
universal, neutral, contact variety of English used beyond national borders, in all spheres of international communication, and providing equal rights to all its speakers, regardless of whether they belong to native or
non-native community. It is argued that, in the contexts of global communication, speakers of International
English constitute the key factor in that they are not passive recipients of the language but interactive agents
performing in the process of language development.